Prenatal diagnosis of aneuploidies in amniotic fluid by multiple ligation-dependent probe amplification (MLPA) analysis - Hamidah N.H.; Munirah A.R.; Hafiza A.; FARISAH A.R.; Shuhaila A.; Norzilawati M.N.; Jamil M.Y.; Ainoon O. (Malaysian Society of Pathologists, 2024)
Indexed by WOS/ Scopus